Factors affecting postpartum contraceptive utilization - Aghniya Misty Mufidah; Niken Meilani; Nur Djanah (Jurnal Kesehatan Ibu dan Anak, 2021)
Family Planning has an important role in strategies to reduce the risk of maternal death. The study aimed at assessing factors affecting postpartum contraceptive utilization. This study was an observational analysis used cross-sectional approach. It was conducted in Yogyakarta, Indonesia on January to February 2021 with the new contraceptive users as the population. Purposive sampling technique was employed, involving 50 respondents. Data collected by an online form questionnaire. Data analysis used the Chi-square test and Fisher-exact test, while multivariate analysis used logistic regression. The magnitude of postpartum contraceptive utilization was 52%. There were association between knowledge level (p=0.035), attitude towards postpartum family planning (p=0.011), husband support (p=0.025) and healthcare provider support (p=0.048) with postpartum contraceptive usage. There was no association between the information exposure (p=0.490) with postpartum contraceptive usage. Knowledge level was the most affecting  factor (OR=6.909;95% CI=1.087-43.912; p=0.041). Attitude towards postpartum family planning and husband support were the confounding factors between knowledge level and postpartum contraceptive utilization. Women with good knowledge, good attitude towards postpartum family planning and husband support has probability 80,8% to use postpartum contraceptive.  The knowledge level is the most affecting factor in postpartum contraceptive use.